CRISPR/Cas12a Based Rapid Molecular Detection of Acute Hepatopancreatic Necrosis Disease in Shrimp - Li, Chenglong; Lin, Nan; Feng, Zhihua; Lin, Minhua; Guan, Biyun; Chen, Kunsen; Liang, Wangwang; Wang, Qiaohuang; Li, Miaomiao; You, Yu; Chen, Qi (Frontiers in Veterinary Science, 2022)
Acute hepatopancreatic necrosis disease (AHPND), formerly called early mortality syndrome (EMS), causes high mortality in cultured penaeid shrimp, particularly Penaeus vannamei and Penaeus monodon. AHPND is mainly caused by Vibrio species carrying the pVA1 plasmid encoding the virulence genes Photorhabdus insect-related (pir) pirVPA and pirVPB. We developed a new molecular assay that combines recombinase polymerase amplification (RPA) and CRISPR/Cas12a technology (RPA-CRISPR/Cas12a) to detect pirVPA and pirVPB, with a fluorescent signal result. The fluorescence RPA-CRISPR/Cas12a assay had a detection limit of 20 copies/µL for pirVPA and pirVPB. To improve usability and visualize RPA-CRISPR/Cas12a assay results, a lateral flow strip readout was added. With the lateral flow strip, the RPA-CRISPR/Cas12a assay had a lower limit of detection of 200 copies/μL (0.3 fmol/L). The lateral flow assay can be completed in two hours and showed no cross-reactivity with pathogens causing other shrimp diseases. In a field test of 24 shrimp samples, the RPA-CRISPR/Cas12a lateral flow assay showed 89% positive predictive agreement and 100% negative predictive agreement. As the new RPA-CRISPR/Cas12a assay is rapid, specific, and does not require complicated experimental equipment, it may have important field applications for detecting AHPND in farmed shrimp.